Economic Assessment of Quality-Related Revenue Loss in a Closed-House Layer System: An Opportunity Cost Analysis - Wahidiyah, Synta Nur; Huang, Wen Chi; Prafitri, Rizki; Nuningtyas, Yuli Frita (Jurnal Ilmu-Ilmu Peternakan, 2026)
This study evaluates the technical performance and economic implications of egg quality degradation in a closed-house layer system at UB Teaching Farm, Indonesia, across three production cycles (2020–2024). While automated systems are designed to optimize efficiency, hidden revenue leakage due to quality attrition is frequently overlooked in traditional financial analyses. Weekly production records were analyzed to quantify degraded egg rates and financial attrition using an opportunity cost framework. Differences in quality-related attrition across production cycles were evaluated using One-Way Analysis of Variance (ANOVA). The research quantified revenue loss resulting from the price disparity between Grade A eggs and abnormal (cracked/damaged) eggs. Results showed a total cumulative volume of 2,473 kg of abnormal eggs across the three cycles. Due to a contractual price agreement that limited the price gap to IDR 1,000/kg, the total cumulative revenue loss was contained at IDR 2,488,300. Economically, the study identified a cumulative revenue loss (P<0.05). Although physical attrition is below the 1% threshold, this loss represents a direct reduction in net profit margins and is equivalent to the cost of approximately 355 kg of high-quality layer feed. This study concludes that sustainable poultry management in closed-house systems requires not only advanced technology but also rigorous mechanical maintenance and data-driven interventions to mitigate quality-related financial leakage.